Reproducibility of intravascular ultrasound radiofrequency data analysis (virtual histology) with a 45-MHz rotational imaging catheter in ex vivo human coronary arteries. Issue 2 (February 2015) - Muramatsu, Takashi; García-García, Hector M.; Brugaletta, Salvatore; Heo, Jung Ho; Onuma, Yoshinobu; Fedewa, Russell J.; Nair, Anuja; Ozaki, Yukio; Serruys, Patrick W.
Abstract Background Despite the frequent use of spectral analysis of intravascular ultrasound radiofrequency data (VH® IVUS) in clinical studies, the assessment for reproducibility using this with high frequency IVUS remains unexplored. Purpose The aim of this study was to examine the reproducibility of VH IVUS using 45-MHz rotational IVUS in ex vivo human coronary arteries. Methods Data were collected using 45-MHz VH IVUS (Revolution®, Volcano Corporation, San Diego, CA, USA) via a series of pullbacks from eight human coronary artery specimens. Imaging data were analyzed by two independent observers. Intraobserver and interobserver reproducibility were assessed using five pullbacks from five vessels. The intercatheter reproducibility was assessed using three different catheters in each of the five vessels. The intracatheter reproducibility was assessed between the two sequential pullbacks from each of the 15 catheters used in the intercatheter assessment. Results Geometrical measurements consistently showed low variability (relative difference <10%) and excellent intraclass correlation coefficients (ICCs), ranging from 0.88 to 1.00. With respect to the compositional measurements, the relative differences were predominantly higher than those of geometrical measurements. In particular, fibrous-fatty area showed a higher relative difference (17.5% in intercatheter assessment) compared to fibrous, necrotic core, and dense calcium areas (6.5%, 8.4%, and 6.4%, respectively). However, each compositional measurement also showed acceptable reproducibility (ICCs ranging from 0.82 to 1.00). Conclusions The 45-MHz rotational VH IVUS technology had acceptable reproducibility with respect to geometrical and compositional assessments in ex vivo human coronary arteries. These data are crucial when designing future longitudinal studies addressing geometrical measurements and plaque characterization by 45-MHz VH IVUS.